Gender differences in hospitalised patients' perceived reasons for their depression. (10th July 2013) - Gaudiano, Brandon A.; Nowlan, Kathryn; Hughes, Jessica A.; Miller, Ivan W.
Abstract Background Perceived causes of depression can affect treatment preferences and outcomes. Men and women may have somewhat differing views about the causes of their depression, but there is a paucity of research on gender differences in hospitalised patients with depression. Aims We examined potential gender differences in hospitalised patients' perceived causes for their depression and their relationship with treatment beliefs and preferences. Method A sample of 52 psychiatric inpatients hospitalised with depression was recruited and completed self-report measures of reasons for depression, depression severity, treatment beliefs and preferences. Results Biological reasons for depression were associated with more severe depression and more positive medication beliefs. In addition, results showed that women were significantly more likely to endorse physical and biological reasons for their depression compared with men. Gender moderated the relationship between physical reasons for depression and medication beliefs, such that men endorsing physical reasons found antidepressants less acceptable and had more negative beliefs about medication compared to women. Conclusions Findings indicate that depressed men and women in the hospital may have differing views about the causes of their depression and this may affect the acceptability of treatments. Depression treatment in inpatient settings should be better personalised to match the beliefs of individual patients.